Assessment of the Influence of Mine Waters on Surface Water Quality in Ostrava-Karvina Region - SYROVÁ, Lucie; BALCAŘÍK, Lukáš; ŠIMÁČKOVÁ, Bohdana; SHAGHAGHI, Samaneh (GeoScience Engineering, 2022)
The study deals with the evaluation of the effects of mining water on surface water quality in the Ostrava-Karvina region. The rivers were monitored from March 2019 to February 2021 and results were evaluated according to Government Regulation No. 401/2015 Coll. Mine waters are primarily loaded with dissolved substances, namely chlorides. Among others, the study focuses on parameters like temperature, pH, conductivity, sulphates, suspended solids, iron, manganese and radioactivity. The influence of mine water outlets was proven in the study, namely the influence of Jeremenko Water Pit on the monitored area of Ostravice River and the influence of Karvinský Potok tributary on the monitored area of Olše River. The Orlovská stružka did not have such a demonstrable effect on the monitored area of Odra River as the aforementioned outlets on other rivers. Keywords: Influence of mine waters; Karvinský potok; Mine waters; Orlovská stružka; Water Pit Jeremenko.